Avascular Necrosis and Time to Surgery for Unstable Slipped Capital Femoral Epiphysis: A Systematic Review and Meta-analysis. Issue 10 (9th November 2022) - Ibrahim, Talal; Ball, Matthew; Riaz, Muhammad; Kenawey, Mohamed
Abstract : Background: Avascular necrosis (AVN) is a well-known complication of unstable slipped capital femoral epiphysis (SCFE) and its cause is multifactorial. Higher AVN rates have been reported with surgery undertaken between 24 hours to 7 days from the onset of symptoms. The current evidence regarding time to surgery and AVN rate remains unclear. The aim of our study was to investigate the rate of AVN and time to surgery in unstable SCFE. Methods: A literature search of several databases was conducted. Eligibility criteria included all studies that reported AVN rates and time to surgery in unstable SCFE patients. We performed a meta-analysis using a random-effects model to pool the rate of AVN in unstable SCFE using different time to surgery subgroups (≤24 h, 24 h - 7 d and >7 d). Descriptive, quantitative and qualitative data were extracted. Results: Twelve studies matched our eligibility criteria. In total, there were 434 unstable SCFE of which 244 underwent closed reduction (CR). The pooled AVN rates were 24% [95% CI: 16%-35%] and 29% [95% CI: 16%-45%] for the total and CR groups, respectively. The highest AVN rates were with surgery between 24 hours to 7 days, 42% and 54% for the total and CR groups, respectively. The lowest rates of AVN were with time to surgery ≤24 hours (22% and 21% respectively) and >7 days (18% and 29% respectively). These differences were not statistically significant. There was significant subgroup heterogeneity which was highest in the 24 hours - 7 days subgroup and lowest in the >7 days subgroup. Conclusions: The cumulative evidence was not conclusive for an association between AVN rate and time to surgery. The overall AVN rates were lower in unstable SCFE patients who had surgery ≤24 hours and >7 days. However, treatment techniques were very variable and there was significant heterogeneity in the included studies. Multi-centre prospective studies are required with well-defined time to surgery outcomes. Level of Evidence: Level III/IV.